Enhancing Student Literacy With the “Go to Mier” and Reading Corner Program at SD Muhammadiyah 3 Wage: Penguatan Literasi Siswa Dengan Program Go To Mier Dan Pojok Baca Di SD Muhammadiyah 3 Wage - Nuroh, Ermawati Zulikhatin; Arumdani, Dewi Kirana Putri; Anggraeni, Alvina Rizky Dwi; Septiani, Wulan Dwi; Farahdiba, Everyana Frienansia (Universitas Muhammadiyah Sidoarjo, 2024)
This article aims to evaluate the effectiveness of the